2019
DOI: 10.1177/0309364618792718
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of foot orthoses on Star Excursion Balance Test performance in patients with chronic ankle instability

Abstract: Foot orthoses improve reach distances in patients with chronic ankle instability. Custom-molded with textured surface foot orthosis has a more pronounced effect compared with other foot orthoses. Clinical relevance The custom-molded foot orthosis with textured surface could be an effective device to improve dynamic balance in chronic ankle instability (CAI) patients. It may be considered as an efficient intervention to reduce ankle sprain recurrence in these individuals, although further research should be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Previously, mainly the effects of passive anklefoot orthoses or prophylactic ankle braces on functional reach in the star excursion balance test have been examined. Those studies showed that dynamic balance did not differ among different orthotic conditions in healthy people (Hadadi et al, 2014;Willeford et al, 2018), however that in ankle instability patients functional reach distance can be significantly increased when compared to no-orthosis condition (Hadadi et al, 2014;Crockett and Sandrey, 2015;Abbasi et al, 2019). Contradictory results are reported for dynamic proactive balance.…”
Section: Tendency Of An Impaired Dynamic Reactive Balancementioning
confidence: 97%
“…Previously, mainly the effects of passive anklefoot orthoses or prophylactic ankle braces on functional reach in the star excursion balance test have been examined. Those studies showed that dynamic balance did not differ among different orthotic conditions in healthy people (Hadadi et al, 2014;Willeford et al, 2018), however that in ankle instability patients functional reach distance can be significantly increased when compared to no-orthosis condition (Hadadi et al, 2014;Crockett and Sandrey, 2015;Abbasi et al, 2019). Contradictory results are reported for dynamic proactive balance.…”
Section: Tendency Of An Impaired Dynamic Reactive Balancementioning
confidence: 97%
“…Five studies also included healthy controls, with a total of 79 participants. Both male and female subjects were included in 13 studies [ 10 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and 5 studies did not report the gender of the subjects [ 11 , 45 , 46 , 47 , 48 ]. The subjects were all young adults aged between 18 and 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects were all young adults aged between 18 and 30 years. The time from the first sprain to the test was at least 12 months in 9 studies [ 10 , 11 , 35 , 36 , 39 , 40 , 42 , 47 ], the first sprain occurred within 12 months in one study [ 34 ], and the first sprain occurred within 6 months in one study [ 45 ]. However, seven studies did not report the time from the first sprain to the test for the participants [ 28 , 37 , 38 , 41 , 43 , 44 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although these orthoses do not directly rectify the issue, they do prevent the negative consequences of ankle laxity by providing the external support needed to correct ankle motion as shown by some studies, especially when custom-molded orthoses are used. 28,29 In fact, when evaluating inversion angles and velocity at the ankle, there was a significant reduction in both parameters with the use of bracing treatment. 30 Physical therapy traditionally focuses on strengthening of the peroneal muscles prevent inversion injuries and closed chain activity to help optimize foot strike and mechanics.…”
Section: Management Nonsurgicalmentioning
confidence: 98%